PENGARUH PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD MELALUI AKUNTABILITAS PUBLIK SEBAGAI VARIABEL INTERVENING - Annisa Hakim Purwantini; Siti Noor Khikmah (Universitas Ahmad Dahlan, 2014)
This research is aimed to investigate whether internal control have signifi cant effect to fraud prevention using public accountability as intervening variabel. The data in this research is the primary data, which obtained by distributing questionnaires directly to respondents, Inspectorate auditors of the city as ex-Kedu residency. Amount of sampel is 59 Inspectorate auditors that be selected by using purposive sampling method. Hypothesis testing was done by path analysis. This research shows that internal control signifi cantly affect to public accountability and fraud prevention. Using path analysis found that internal control can directly infl uence to fraud prevention and also have indirectly affect from internal control to public accountability (as intervening) and to fraud prevention. The value of R2 public accountability is 56.9%, it means that public accountability level is explained by the variable of internal control 56.9%, while the other 43.1% is explained by other variables. However, the value of R2 fraud prevention is 75.8%, it means that fraud prevention level is explained by the variable of internal control 75.8%, while the other 24.2% is explained by variables excluded from the model.